Pengaruh Beberapa Pestisida Nabati Dalam Menekan Kejadian Penyakit Antraknosa Pada Cabai Rawit Hiyung Di Desa Tajau Landung - Nisa Syafitriyani; Elly Liestiany; Dewi Fitriyanti (JURNAL PROTEKSI TANAMAN TROPIKA, 2022)
Research on the use of several botanical pesticides from karamunting leaves, kramai leaves and rhizomes (turmeric, sand ginger and galangal) on cayenne pepper hiyung in Tajau Landung Village. Cayenne pepper (Capsicum frustescens L.) is a typical commodity of South Kalimantan, and one of the local varieties is known as hiyung chili. One of the causes of the decrease in chili production both in quality and quantity is anthracnose disease caused by Colletotrichum sp. This study aims to determine the effect of several vegetable pesticides in suppressing the incidence of anthracnose disease in Hiyung cayenne pepper in the swamp land of Tajau Landung Village. A total of 20 separate experiments were carried out, all of which followed a Completely Randomized Design (CRD) with 4 treatments and 5 replications each. The growth parameters measured were chili plant height, number of chilies, chili fruit weight and the incidence of anthracnose disease in chilies. The results of this study were the application of biologicalpesticides, karamunting and rhizomes (turmeric, sand ginger and galangal) were able to suppress anthracnose disease compared to the control treatment. However, in each treatment, karamunting and rhizomes (turmeric, kencur and galangal) had the same effect in reducing the spread of anthracnose in Hiyung cayenne pepper as grown in Tajau Landung.